Penerapan Metode Eksperimen Untuk Meningkatkan Aktifitas Dan Hasil Belajar IPA Materi Energi Dan Penggunaannya Pada Siswa Kelas IV SDN 219 Bengkulu Utara - Rokhmad, Rokhmad (Yayasan Darussalam Bengkulu, 2022)
The purpose of this study was to improve the learning outcomes of grade IV A students in science learning through the application of the experimental method of energy material and its use in SD Negeri 219 Bengkulu Utara in the 2018/2019 academic year. The research design used was classroom action research (PTK). In this study, the subjects were 22 students of grade IV A SD Negeri 219 Bengkulu Utara. The results showed that there was an increase in student activity in each cycle of 16.67%, from 66.66% in the first cycle to 83.33% in the second cycle. Likewise, student learning outcomes have increased by 45.47%. In the first cycle students who completed learning reached 31.80%, while in the second cycle it reached 77.27%. In the first cycle there were 15 students who scored below the KKM 75, and only 7 students who got the same score and above the KKM. The average score of students only reached 65.31. Furthermore, in the second cycle only 5 students who scored below the KKM, and 17 students who got the same score or above the KKM. The average score of students reached 77.03